n-Butanol or isobutanol as a value-added fuel additive to inhibit microbial degradation of stored gasoline - James G. Elkins; Miguel Rodriguez, Jr; Olivia N. Cannon; Raynella M. Connatser; Gbekeloluwa B. Oguntimein; Michael D. Kass; Brian H. West; Brian H. Davison (Fuel Communications, 2022)
Biofouling of gasoline can occur during fuel storage caused by bacteria and fungi that form a biofilm at a fuel/water interface and that produce organic acids and sulfides. Fuel additives are applied to gasoline to prevent biofouling but are relatively expensive, are not always effective against biofilms, and do not contribute to the combustibility of gasoline. Bio-isobutanol is an approved, certified advanced biofuel and is added up to 16% (v/v) in gasoline blends “iBut16”; n-butanol blends are currently under review. Microorganisms are inhibited by n-butanol or isobutanol when the aqueous concentration reaches >2-3% (w/v). We determined that n-butanol partitions into the aqueous phase of a model gasoline/water system reaching concentrations of 42 g/L and up to 48 g/L from gasoline blends at 10% and 24% (v/v), respectively. Likewise, isobutanol blended in gasoline at 10% and 24% (v/v) partitioned into an aqueous phase at 45 g/L and 53 g/L, respectively. Several bacterial and fungal strains that originate from fuel storage tanks, or are known to be solvent tolerant, were evaluated for their potential growth in a range of n- and isobutanol concentrations. Growth rates for all strains tested were reduced by 40–100% relative to untreated controls in n- and isobutanol concentrations of 1.5 and 2.0% (v/v). No observable growth occurred for any of the microorganisms in solvent concentrations at 3.0% (v/v). T amphiphilic and chaotropic properties of n- or isobutanol help them inhibit microbial growth and could serve as effective biocides during fuel storage as well as being valuable fuel additives.